Analysis of incidents of violence in a large italian hospital - Sossai, Dimitri; Molina, Francesco Stefano; Amore, Mario; Ferrandes, Giovanna; Sarcletti, Elena; Biffa, Gabriella; Accorsi, Simone; Belvederi Murri, Martino; Tomellini, Marzia Jole; Copello, Francesco (La Medicina del Lavoro, 2017)
Introduction: An increase in the rate of non-fatal violence events, from 20.65/10,000 in 2012 to 22.81/10,000 in 2014, was observed at the IRCCS Ospedale Policlinico San Martino in Genoa. Objectives: To analyze the incidence and outcome of the phenomenon of violence, by identifying the type of aggressive event and the ward in which it occurred, assuming that the occurrence is evenly distributed and not only limited to the psychiatric or to the emergency department. The age and sex of both attackers and victims of aggression were also analyzed. Methods: Retrospective analysis: study of injury trends related to episodes of violence between 2012 and 2015, incidence compared to other injuries and evaluation of the direct costs. Observational staff surveys with a questionnaire based on the Overt Aggression Scale and statistical data analysis. Results: Following the aggressions, 36 injuries were identified over the study period (2012-2015), resulting in 431 days of absence from work. The direct estimated costs were € 64,170. The observational surveys of each ward showed a high concentration of events. Reports were received from 34 out of the 76 evaluated wards. Seventy-five percent of the reports concerned only four operative units: emergency room, intermediate care, psychiatry and geriatrics. Sixty-one percent of the questionnaires were filled out by nurses, 23% by support staff and the remaining 16% was provided by physicians and coordinators. Conclusions: Violence against healthcare workers is a well-known problem; action is required on the scheduling of activities, improvement of communication paths with users and the training of operators.